1998
DOI: 10.1038/sj.onc.1201985
|View full text |Cite
|
Sign up to set email alerts
|

The chimeric protein, PEBP2β/CBFβ-SMMHC, disorganizes cytoplasmic stress fibers and inhibits transcriptional activation

Abstract: The chromosomal inversion 16(p13;q22) associated with human acute myeloid leukemia generates the chimeric PEBP2b/CBFb-SMMHC gene. The PEBP2b/CBFb portion of the chimeric polypeptide harbors most of the amino acid sequence of the PEBP2b/CBFb protein, the non-DNA binding subunit of the heterodimeric transcription factor, PEBP2/CBF, whereas the SMMHC portion of the chimera consists of the rod domain of the smooth muscle myosin heavy chain molecule. In this study we examined the subcellular localization of the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…We previously reported that the transient expression of the PEBP2␤/CBF␤-SMMHC protein in the C2C12 myoblast cell line resulted in drastic morphological changes and the presence of protein in the cell membrane and nuclear subfractions. 23 We suggested the disorganization of the cytoplasmic stress fibers observed in the transfected C2C12 cells to be somehow related to the membrane localization of chimeric protein. The dual functions exerted by the membrane-and nuclear-located PEBP2␤/CBF␤-SMMHC protein that we proposed previously may be applicable to leukemic cells carrying inversion 16 and may provide a clue to unraveling the molecular mechanisms of myeloid leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the transient expression of the PEBP2␤/CBF␤-SMMHC protein in the C2C12 myoblast cell line resulted in drastic morphological changes and the presence of protein in the cell membrane and nuclear subfractions. 23 We suggested the disorganization of the cytoplasmic stress fibers observed in the transfected C2C12 cells to be somehow related to the membrane localization of chimeric protein. The dual functions exerted by the membrane-and nuclear-located PEBP2␤/CBF␤-SMMHC protein that we proposed previously may be applicable to leukemic cells carrying inversion 16 and may provide a clue to unraveling the molecular mechanisms of myeloid leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…23 Briefly, the cells were suspended in a buffer containing 10 mM Hepes-KOH, pH 7.6, 10 mM KCl, 1.5 mM MgCl 2 , 0.5 mM dithiothreitol, 1 mM EDTA, 1 mM EGTA and 1 mM phenylmethylsulfonyl fluoride (PMSF). The cell suspension was homogenized in a Dounce homogenizer and the mixture was centrifuged at 1000 g for 10 min at 4°C.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…The PEBP2b-MYH11 gene is observed in the inverted chromosome 16(p13;q22) associated with human acute myeloid leukemia and produces a chimeric protein of PEBP2b/CBFb and smooth muscle myosin heavy chain. This chimeric protein interacts with the runt domain of the a subunit and deregulates PEBP2/CBF in a dominant interfering manner (Liu et al, 1993Claxton et al, 1994;Cao et al, 1997;Tanaka et al, 1998). PEBP2b/ CBFb knock-out mice as well as PEBP2b-MYH11 knocked-in mice showed essentially the same phenotype as the AML1/PEBP2a/CBFa2 knock-out mice (Castilla et al, 1996;Sasaki et al, 1996;Wang et al, 1996b;Niki et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…59,83,84 This may result from increased affinity of CBF␤-SMMHC for the cytoskeleton, compared with CBF␤, perhaps as a result of interaction of its SMMHC segment with cytoskeletal-associated non-muscle myosins. 85 CBF␤-SMMHC:CBF␣ complexes retain the ability to bind DNA. 77,81 Therefore, CBF␤-SMMHC might also interfere with CBF␣ trans-activation via local effects on promoter/enhancer transcription complexes.…”
Section: Cbf␤-smmhcmentioning
confidence: 99%